Accounting and the management of internal interdependencies: 14th century archival sources from the Comune of Siena - Andrea Giorgi; Elena Giovannoni; Stefano Moscadelli; Angelo Riccaboni (JLIS.it, 2019)
The aim of this study is to explore the role that accounting systems effectively played in managing the internal relationships among the various administrative bodies of the Comune (City State) of Siena in the 14th century. This period was characterized by an ever increasing need to monitor economic activities, a need perceived by the Comune with regard to all those who were entrusted with the management of public funds. In particular, in 1358 an office was created specifically to review the accounts of the camarlenghi (who were in charge of the management of public funds) nominated by the Comune of Siena. The office was originally staffed by three temporary Riveditori (auditors) and later by a permanent commission of Regolatori (regulators). On the basis of archival sources, so abundant on 14th century Siena, this paper analyses the changing relationships among the various administrative bodies of the Comune, in particular detail the Gabella generale and the Biccherna (which were the offices in charge of managing the main cash inflows and outflows pertaining to the administration of the Comune) and the activities of the Regolatori. By interpreting accounting systems as a set of rules (i.e., the formalised statements of procedures), roles (the network of social positions), and routines (the practices habitually in use), the present study shows that, since the Middle Ages, accounting has played a central role in the management of internal interdependencies and in the construction of organisational order. In the case of the Comune in the 14th century, accounting practices were capable of regulating, legitimising and balancing relations of power, dependency and autonomy among the different bodies of the same organisation.